Stunting and blood lead levels in a non-industrial rural area: the role of microminerals in child growth risk assessment - Maya Safitri; Lia Amalia; Benny Permana; Dida Achmad Gurnida (Pharmacia, 2025)
Stunting remains a major public health issue in low-resource settings, with emerging evidence linking it not only to nutritional deficiencies but also to environmental toxicants such as lead. Despite this, limited research has explored the interplay between lead exposure, microminerals, and child growth in non-industrial rural areas. This study aimed to investigate the association between blood lead levels (BLLs), essential microminerals (zinc, manganese, and iron), and stunting in children, while also identifying environmental sources of lead. A cross-sectional study was conducted among 58 children aged 0–59 months in Datar Village, Central Java, Indonesia. Anthropometric assessments and venous blood samples were collected, and trace elements were quantified using ICP-MS. Lead content in environmental samples (water, food, foliage, soil, and paint dust) was also analyzed by ICP-MS. BLL ≥5 μg/dL was found in 55.2% of children, with manganese levels exceeding the safe threshold in 67.2% of children. Normal zinc levels were found in 91.4% of subjects, while iron deficiency was detected in 65.5% of subjects. No significant association was observed between trace element levels and height-for-age Z-scores. Environmental analysis revealed excess lead in spinach, foliage (longan, hairy fruit), soil samples, and some paint dust samples. Elevated BLL and widespread micronutrient deficiencies may co-exist in non-industrial rural environments and contribute to child health risks. Integrated environmental monitoring is recommended.